Analysis of relationship between production factors to common carps (cyprinus carpio) enlargement pond production in east panti village panti district pasaman regency West sumatera province - Afriantoni, Firli; Ramli, Muhammad; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on September 2013. This study aimed to determine the correlation between stocking density of seed production (X1), feed pellets (X2), fish farmers experience (X3) and the outpouring of hours of work (X4) on the common carps enlargement pond production. The method used in this study is a survey method with the number of respondents 34 people were taken by simple random sampling of 170 farmers common carps enlargement pond.From the results of multiple linear regression of each production factor to common carps enlargement pond in East Panti Village acquired the production function Y= –0.320+0.022X1+0.905X3+0.027X3–0,008X4. With a regression coefficient (R) was 0.973 and a coefficient of determination (R2) was 0.946. The relationship of production factor common carps enlargement pond had a very strong unindirectional relationship to the production enlargement pond production (sig. = 0.000) so that the factors are key in common carps enlargement ponds business while X4 had the weak trade-offs (sig. = 0.070) or had an excess of working hours.Keywords: Relationship Analysis, Factor Production, Production, Common Carps.